BOOTSTRAP RESPONSIVE WEB DEVELOPMENT - JAKE SPURLOCK; DAVE WINER (MUMBAI O' REILLY SPD PVT LTD, 2019)
Bootstrap, as a front-end framework, primarily covers subjects related to web design and development, focusing on creating responsive and visually appealing user interfaces.
BOOTSTRAP
COMPUTERS
CSE & CSM & CSD
Keywords: WEB DEVELOPMENT; COMPUTERS